Bioactive constituents from lengkuas ranting (Alpinia conchigera) - Md. Sukari, Mohd Aspollah; Tang, Sook Wah; Rahmani, Mawardi; Lajis, Md. Nordin; Ali, Abdul Manaf (Sarawak Biodiversity Centre, 2008)
Zingiberaceae is one of the most important herbaceous species found in tropical forests which comprises about 52 genera with 1500 species in the world. Isolation work on crude extracts of Alpinia conchigera yielded p-hydroxycinnamaldehyde and β-sitosterol-3-O-β-D-glucopyranoside which are new to the species besides β-sitosterol. Extracts and p-hydroxycinnamaldehyde were subjected to cytotoxic testing against different cancer cell lines (HL-60, MCF-7, HeLa and HT-29) as well as antimicrobial testing. Crude hexane, chloroform and ethyl acetate extracts were strongly active against Salmonella choleraesuis in antimicrobial assay. In antifungal screening test, hexane extract showed slight inhibition on Aspergillus ochraceaus and Saccharomyces cerevisiae while ethyl acetate extract was active towards S. cerevisiae. All crude extracts except methanol extract exhibited very strong activity in cytotoxic screening test against HL-60 cell line (human promyelocytic leukemia) with IC50 values < 5 μg/mL. p- Hydroxycinnamaldehyde is cytotoxic against all cancerous cell lines tested and strongly active in antimicrobial testing.